Pension Fund Calculation Using Projected Unit Credit, Entry Age Normal, and Attained Age Normal Method (Case Study : PT. Taspen (PERSERO) Cabang Pematang Siantar 2022) - Julianty, Dila Tirta; Listiani, Amalia; Manurung, Chintya Carissa (International Journal of Scientific Research in Science, Engineering and Technology, 2023)
Pension fund (pension plan) is the determination that the employer (company) provides benefits (payments) to employees after they retire for the services that provided while still working. The purpose of establishing a pension funds program is to fulfill the employer’s obligation, to guarantee the retirement period of the employees in the future, and to finance national development to create social welfare. In this study aim to determined normal costs and actuarial liabilities using the three methods consist of Projected Unit Credit (PUC) method, Entry Age Normal (EAN) method, and Attained Age Normal (AAN) method. The data used in this research is the information by PT. Taspen (Persero) Cabang Pematang Siantar such as date of birth, date of started work, basic salary, and the total of pension fund collected in the previous year. Otherwise, the data mortality rate of the employees from the 2022 employment mortality table (TMJ 2022) by PT. BPJS Ketenagakerjaan is also used. The result show that the best method for pension funds program in PT. TASPEN (Persero) Cabang Pematang Siantar is PUC method since the amount of unfunded actuarial liabilities (UAL) has the biggest difference between total actuarial liabilities and the amount that has been funded. It means that the pension funds program can give more surplus than the other methods.
Keywords: Pension Funds; Unfunded Actuarial Liabilities; Attained Age Normal; Projected Unit Credit; Entry Age Normal